Fiscal Justice and the Principle of Direct Benefit in Regional Budget Politics: A Comparison of Motor Vehicle Tax Utilization in Two Provinces - Derriansya Putra Jaya; Arie Wijaya; Aris Munandar (CV. Era Digital Nusantara, 2026)
This study analyzes the extent to which the Motor Vehicle Tax (PKB), as a regional tax, reflects the principles of fiscal equity and direct benefit in provincial budget policy. Using a comparative study design between West Java and South Sumatra Provinces in the 2025–2026 fiscal year, this study evaluates the consistency between PKB revenue and road infrastructure spending through the fiscal conversion ratio indicator. A qualitative approach based on analysis of regional budget documents, regulations, budget realization reports, and policy communications is used to integrate normative and institutional dimensions within a single evaluative framework. The findings indicate two models of PKB utilization. West Java exhibits a trend toward benefit-consistent budgeting with a relatively high fiscal conversion ratio and a strengthening of sectoral associations between taxes and road construction. In contrast, South Sumatra applies a more flexible general allocation budgeting model across sectors, but with a looser direct benefit association. This study also expands the concept of fiscal equity through the spatial dimension by introducing the urban–rural fiscal return gap and emphasizing the importance of fiscal sustainability in addressing potential tax base erosion in the transportation sector. The main contribution of this research is the operationalization of the fiscal conversion ratio as an evaluative indicator of the benefit principle at the subnational level, as well as the assertion that fiscal justice is the result of political allocation choices in a decentralized system.